Identification of"Methyl Formate-Producing Enzyme" in Cell-Free Extract of Pichia Methanolica = Identifikasi"enzim pembentuk metil formar" dari ekstrak sel Pichia methanolica - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1993)
ABSTRACT: Cell-free synthesis of methyl formate by extract of Pichia methanolica was investigated. It was observed that the addition of formaldehyde could increase the methyl formate-producing activity compared to control experiment which contained methanol as a sole substrate for methyl formate production. On the other hand, the addition of formic acid, formate, and S-formylglutathione or GSH did not increase the activity. Methyl formate-producing activity disappeared upon gel filtration of the cell-free extract on Sephadex G-25. However, the full activity was recovered with the addition of NAD+. These results indicated that methyl formate-producing enzyme was present in cell-free extract. This enzyme was found to be responsible for methyl formate formation from methanol and formaldehyde when its cofactor (NAD+) was available. Based on this finding, the standard assay system for methyl formate-producing enzyme could be constructed. Purification of methyl formate-producing enzyme from cell-free extract was possible due to the availability of the standard assay system constructed in this experiment.